A strategic plan for the Workers Cooperative of the Philippines - Sumalpong, Rhesababes G.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2009)
The Workers Cooperative of the Philippines started to operate in 1995 engaging in micro-lending activity. For more than a decade of existence, it has gained financial growth and organizational development but currently it is confronting issues such as slow growth in membership, low collection efficiency and saturated ?market saturation? in the lending business. Problem in collection efficiency is characterized by piling up of past due accounts in loan receivable. The lending business market is limited to the members of the cooperative thus, slow growth in membership signify ?saturation? of its market. In 2005, it started to operate the water refilling station. Performance of the water refilling station in the first year of operation did not give positive return. However, it started to generate income in the succeeding years but did not satisfactorily meet the members? expectation. It is a challenge now to the cooperative officers how to make the water refilling generate the maximum profits. In solving the problems mentioned, the existing objective of the cooperative is reviewed including its corporate governance, the internal and external environment of the cooperative were analyzed to come up with a strategies to be used to help solve those problems which has a long-term effect to the very existence of the cooperative. Secondary data were gathered to help evaluate the external environment of the cooperative. Interviews were made and first hand data From the cooperative were collected to help analyze the internal environment of the cooperative. Policies are reviewed and practices of the cooperative are observed. The process of evaluating the internal and external environment of the cooperative until strategies were chosen follows the framework of Thomas L. Wheelen and J. David Hunger. The proposed strategies are market development coupled with strengthening the lending and collection policy and procedures, market penetration in the water refilling business and organizational development to align the cooperative?s objectives and structure to the needs of the cooperative. The economic growth for the next five years in General Santos City is an opportunity that the cooperative should take by using those strategies mentioned. It has the advantage to success because of its proactive objectives and market base and marketing intermediaries, the membership. The proposed programs are expected to increase the cooperative net profit by an average of 15.7% annually translating to an average yearly income for next five years of P10,650,000.00. However, the cooperation of the members and their active participation as agents of development is a factor to the success of these programs.
Thesis (Master in Management)--University of the Philippines Mindanao, December 2009.